Gallstone Ileus of the Colon: Leave No Stone Unturned. (22nd July 2013) - Salemans, P. B.; Vles, G. F.; Fransen, S.; Vliegen, R.; Sosef, M. N.
Abstract : A case of gallstone ileus of the colon with illustrative pictures is presented, making the physicians more aware of this rare entity. Furthermore, the use of imaging modalities for diagnosis and decision making in management strategy is discussed.